2014
DOI: 10.1007/s00438-014-0857-x
|View full text |Cite
|
Sign up to set email alerts
|

Bicluster pattern of codon context usages between flavivirus and vector mosquito Aedes aegypti: relevance to infection and transcriptional response of mosquito genes

Abstract: The mosquito Aedes aegypti is the primary vector of dengue virus (DENV) infection in most of the subtropical and tropical countries. Besides DENV, yellow fever virus (YFV) is also transmitted by A. aegypti. Susceptibility of A. aegypti to West Nile virus (WNV) has also been confirmed. Although studies have indicated correlation of codon bias between flaviviridae and their animal/insect hosts, it is not clear if codon sequences have any relation to susceptibility of A. aegypti to DENV, YFV and WNV. In the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Therefore, versatility in gene expression and protein synthesis is at premium, and certain changes in the viral RNA genome could affect the fitness of the virus in a specific host. Indeed, viral fitness changes relate to dinucleotide frequencies, codon preferences, and codon pair biases [ 5 , 14 , 15 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, versatility in gene expression and protein synthesis is at premium, and certain changes in the viral RNA genome could affect the fitness of the virus in a specific host. Indeed, viral fitness changes relate to dinucleotide frequencies, codon preferences, and codon pair biases [ 5 , 14 , 15 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ecology, different virus-host relationships and biogeographical migrations of flavivirus species may explain observed genetic differences among subgroups [ 13 , 15 , 16 , 55 , 56 ]. Phylogenetic studies have acknowledged three groups that reflect the evolutionary and ecological dynamics: tick-borne, mosquito-borne ( Aedes and Culex species), and no known-vector flaviviruses [ 57 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Flaviviruses can infect and replicate in hosts of different phyla. Therefore, their versatility in gene expression and protein synthesis and changes in the viral RNA genome could affect the fitness of the virus in a specific host relating to dinucleotide frequencies, codon preferences, and codon pair biases [ 97 , 98 , 99 ]. Nevertheless, ecology, different virus-host relationships, biogeographical migrations of flavivirus species and genetic differences may explain observed differences in flaviviral codon usage preference to human housekeeping genes [ 98 , 100 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that codon context (the propensity of adjacent codons to consistently pair with themselves or another codon) among Asian and American DENV isolates showed a bias toward (A)(A/T)(A)-(A)(A/T)(A) coding sequences and general avoidance of (C/G)(C/A)(C/G)-(C/G)(C/A)(C/G) coding sequences across all four serotypes [119]. In addition to DENV, we also compared [121] the codon context bias of other flaviviruses, including West Nile virus (WNV) and yellow fever virus (YFV), and determined that codon context bias varies in a bicluster manner with A. aegypti genes that have been shown to be differentially expressed following infection by these viruses [92]. This result suggests that codon context sequences of A. aegypti and the flaviviruses may play an important role in determining successful infection by these viruses.…”
Section: Genome Coevolution and Vector Competencementioning
confidence: 99%